Description of the school environment related to physical education classes, recess, extracurricular activities and physical spaces in the city of Pelotas, RS, Brazil - Alan Knuth; Inácio Silva; Pedro Hallal (Revista Brasileira de Atividade Física e Saúde)
The aim of the present study was to describe the school environment of public and private primary schools from the city of Pelotas, RS, Southern Brazil, according to the availability of Physical Education (PE) classes, breaks, extracurricular activities and physical spaces. A cross-sectional study was conducted, including both public and private schools. In each school, the principal or a PE teacher was interviewed to assess PE classes, recess and extracurricular activities, while a checklist was carried out to evaluate the quality and availability of physical spaces.  A total of 71.9% of the 99 schools had PE classes for grades 1 to 4. Extracurricular projects were available in 59.6% of the schools and 71.2% offered free activities to students. The most common activities are dancing and “futsal”. There was a gym in 10.1% of schools (40.0% of private and 4.8% of public schools). Higher availability and quality of outdoor courts, indoor rooms, multimedia rooms and green areas were more consistently found among private schools than public schools. Our findings indicated a low coverage of PE classes in grades 1 to 4, and insufficient availability and quality of physical structures in the public schools, compared to private ones. Many environmental features should be used in order to improve students’ health and well-being.